(untitled) (Biological Sciences - PJSIR, 2024)
Various factors and agents cause mutations and damage to DNA, such as UV radiations, alkylating agents, toxins, aromatic compounds, environmental stress and other ways, including spontaneous base DNA damage. These DNA damages could prove deleterious if left un-repaired, leading to cancer and many other unhealthy conditions. As DNA is the genomic material, repairing the damage is more critically important. However, cells have various mechanisms to cope with the damaged DNA, including DNA polymerase self-correction and proofreading, direct reversal of the chemical changes, readily repairing of double helix, base and nucleotide excision repair and mismatch repairs. This review briefly explains DNA damage and repair mechanisms and the disease states associated with them.